Clinical impact of genetic alterations of CTNNB1 in patients with grade 3 endometrial endometrioid carcinoma. Issue 5 (24th March 2022) - Kobayashi Kato, Mayumi; Asami, Yuka; Takayanagi, Daisuke; Matsuda, Maiko; Shimada, Yoko; Hiranuma, Kengo; Kuno, Ikumi; Komatsu, Masaaki; Hamamoto, Ryuji; Matsumoto, Koji; Ishikawa, Mitsuya; Kohno, Takashi; et al.
Abstract: To identify prognostic factors in patients with grade 3 (high‐grade) endometrial endometrioid carcinoma, we evaluated the spectrum of genomic alterations and examined whether previously reported molecular subtypes of endometrial carcinoma were adapted to clinical outcome prediction. Seventy‐five Japanese patients with grade 3 endometrial endometrioid carcinoma, who underwent a potentially curative resection procedure between 1997 and 2018 at the National Cancer Center Hospital, were included. We classified the patients into four risk groups of the disease based on the Proactive Molecular Risk Classifier for Endometrial Cancer. Genomic alterations in PTEN, ARID1A, TP53, and PIK3CA were detected in more than 30% of the patients. Overall survival and recurrence‐free survival of patients with genomic alterations in CTNNB1 were poorer than those of patients with wild‐type CTNNB1 ( p = 0.006 and p = 0.004, respectively). Compared with that of alterations prevalent in Caucasians, the frequency of genomic alterations in POLE and TP53 was higher in our study than in The Cancer Genome Atlas dataset ( p = 0.01 and p = 0.01, respectively). The tendency for recurrence‐free survival in the POLE exonuclease domain mutation group was better than that in the TP53 mutation and mismatch repair‐deficient groups ( p = 0.08 and p = 0.07, respectively), consistent with the Proactive Molecular Risk Classifier for Endometrial Cancer risk classifier definition. The CTNNB1 mutation is a potential novel biomarker for the prognosis of patients with grade 3 endometrial endometrioid carcinoma, and prognosis classification using Proactive Molecular Risk Classifier for Endometrial Cancer may help screen Japanese patients with the disease. Abstract : CTNNB1 genomic alterations were significantly associated with poor overall and recurrence‐free survival of G3EEC patients. Detected genomic alterations in PTEN (58.7%), ARID1A (52.0%), TP53 (48.0%), PIK3CA (44.0%), and POLE (33.3%) exceeded 30% in G3EEC. Frequency of TP53 and POLE genomic alterations was higher in our study than in TCGA dataset.